Effectiveness of Eracs Method in Accelerate Recovery Against Long Duration of Hospitality - Nurhasanah Nurhasanah (GLOBAL HEALTH SCIENCE GROUP, 2024)
The development of science and technology in the health sector has encouraged many pregnant women to want a labor process with minimal pain. One method that is increasingly popular is delivery by caesarean section. This study aims to evaluate the effectiveness of the ERACS (Enhanced Recovery After Caesarean Section) method in accelerating recovery and reducing the duration of hospitalization after a cesarean section. The research method uses a qualitative approach with a phenomenological design, involving five key informants at Mother and Child Hospital Ananda Trifa, Parepare City. Data were collected through in-depth interviews, observations, and questionnaires from August to September 2024. The results showed that all informants had a good understanding of the ERACS method, with knowledge obtained from doctors and social media. The ERACS method has been shown to be effective in reducing postoperative pain, allowing early mobilization within 6-8 hours, and shortening the duration of hospitalization to an average of two days. Family support and collaboration with the medical team also play an important role in successful recovery. Overall, the ERACS method provides significant benefits in accelerating recovery and increasing patient comfort, making it a promising alternative to cesarean delivery.